Role of Teacher as a Therapist: Issues, Challenges and Reflective Practices - Chellamani, K. (INDIAN EDUCATIONAL REVIEW, 2012)
The competitive era of today lays stress on students. This is caused by unhappy situations created by teachers due to emotional imbalance. Teachers attend only the cognitive components and they do forget the emotive behaviour of students. It is the understanding of the teachers on Neurocognition that brings beneficial changes in the learning environment of the students so as to help them learn. In applied psychological terms we can call it neurocognitive therapy. As a therapist, the teacher takes an active role in guiding his students as he works to develop friendly environment during and after Instructional programme. Hence, the teacher needs to be familiar with the diagnosis and treatment for handling situations and conditions such as anxiety, disorders, depression, learning disabilities and bi-polar disorder. Along with this knowledge base, the teacher should know the strategies for neurocognitive therapy. One of such strategies is reflective practices. The author attempts to illuminate portfolio writing and reflective learning journals, the two essential reflective practices every teacher has to follow for healthy bringing up of future citizens.